SITES OF RELATION AND "TOUT-MONDE": reflections on glissant's late work. Issue 3 (4th May 2019) - Drabinski, John E
Abstract: This essay tracks the movement in Édouard Glissant's work from thinking relationality as creolisation to Relation as such, to a globalised sense of cultural contact and transformation he calls tout-monde . This movement is informed by the critical meaning of the Caribbean as a historical and memorial experience, figured as the archipelago, and governed by chaotic mixture. Chaotic mixture, which is Glissant's preoccupation from his earliest work forward, is generated by the Caribbean as a crossroads of the world; the slave trade, then colonialism, brought irreconcilable yet fecund cultural dynamics to the archipelago and produced creolised forms of culture. What is the significance of these forms of culture? What theoretical lessons are borne by these forms? In the late work, Glissant extends his conception of creolisation, which is initially an internal characteristic of the Caribbean, into the thought of tout-monde. Tout-monde names an aggressive, future-oriented imperative to put global cultures in contact and to draw on the productive chaos that comes from that contact. A poetics of the whole world.